Conceptual Clarity in Clinical Bioethical Analysis. Issue 1 (10th January 2020) - Parker, J Clint
Abstract: Conceptual clarity is essential when engaging in dialogue to avoid unnecessary disagreement and to promote mutual understanding. In this issue devoted to clinical bioethics, the authors exemplify the virtue of careful conceptual analysis as they explore complex clinical questions regarding the essential nature of medicine, the boundaries of killing and letting die, the meaning of irreversibility in definitions of death, the argument for a right to try experimental medications, the ethical borders in complex medical billing, and the definition and modeling of complex disease states.